Empregabilidade dos egressos dos cursos superiores de tecnologia em diferentes regiões do estado de Minas Gerais: o caso do curso de Análise e Desenvolvimento de Sistemas - Giuliano Viana de Alkmin (2015)
This study aims to analyze, through the theme Vocational Education and Labor, the process of inserting and maintaining of the graduates in the Higher Technology Course in Analysis and System Development in the labor market. In the first moment, it was performed a literature review about the relationship among some issues and education such as: employability, neoliberalism, the influence of civil society in public policies, besides the discussion about the Higher Education Courses of Technology. This discussion was focusing on aspects inherent to their legislation, differences between their views and those of traditional courses, their evolutions and the technologist s professional profile. This research was characterized as mixed, once it was based on quantitative and qualitative technique of data collection. The field research was conducted at the Federal Institute of Minas Gerais - Bambuí Campus, Federal Institute of North of Minas Gerais- Januaria Campus, Federal Institute of Mineiro Triangle - Uberaba Campus. It was performed through the electronic application of questionnaire and semi-structured interviews to graduates of that course in these institutions. The results contributed to a confirmation and refutation of the assumptions made at the beginning of this research. Corroboration is linked to evidence that the technologist who graduated in Technology Course in Analysis and System Development, in the Federal Institutes of Minas Gerais, who participated in the study, get a large insertion / maintenance in the labor market, as quantitatively it was proved that in general or by comparative analysis in each campus, the technologists employment rate is high. The refutation is related to the fact that in the informants reports there is no evidence that induces to an understanding that there is an underutilization of the technologists work force, as well as if companies, where these technologists exert their activities, are unaware of the professional profile of these technologists.